On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). IV. Acronicta digna species-complex - Volynkin, Anton V.; Matov, Alexej Yu.; Han, Hui-Lin (Zootaxa, 2017)
The present paper is the fourth in a series of articles on the genus Acronicta Ochsenheimer (Volynkin et al. 2015; Volynkin 2015; Volynkin et al. 2016). In here, we revive A. metaxantha (Hampson 1909) stat. n., which was synonymized with A. digna (Butler, 1881) by Han & Kononenko (2010) to the species level, designate the neotype for Acronycta agnata Draudt, 1937 and revise the synonymy of A. digna and A. agnata.